The Influence of Digital Marketing on Brand Perception among Millennials and Gen Z - Al Akromi, Elok Nur Affah (Politeknik Siber Cerdika Internasional, 2024)
Digital marketing plays a pivotal role in shaping the perceptions of brands, particularly among Millennials and Gen Z, two generations deeply embedded in the digital landscape. As these younger generations increasingly use social media for information, entertainment, and purchasing decisions, brand perception has become inextricably linked to digital engagement. This study examines how digital marketing strategies, including influencer marketing, interactive content, and personalized advertising, influence the way these generations perceive and interact with brands. Through a review of literature and case studies, this paper identifies the key factors that affect brand perception, such as content authenticity, brand values, and the use of social media influencers. Additionally, the paper highlights how brands that effectively engage Millennials and Gen Z can improve brand loyalty, customer trust, and overall business performance. Findings suggest that brands that align their messaging with the values of these generations, such as sustainability and social responsibility, are more likely to foster positive brand perceptions. However, challenges such as content saturation, evolving social media algorithms, and the need for constant innovation remain. The study concludes by offering strategic recommendations for brands looking to enhance their digital marketing efforts and create lasting relationships with these influential consumer groups.